2020
DOI: 10.1155/2020/8831937
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Traditional Chinese Medicine Formula (CoTOL) on Serum Uric Acid and Intestinal Flora in Obese Hyperuricemic Mice Inoculated with Intestinal Bacteria

Abstract: CoTOL is a traditional Chinese medicine (TCM) formula in clinics for treating gout and hyperuricemia, especially in obese patients with recurrent attacks. However, fewer studies have investigated how CoTOL impacts the intestinal flora in reducing uric acid. In the present, we analyze the bacteria targeted by ingredients of CoTOL and evaluate the effects of CoTOL on uric acid and intestinal flora in a mice model of obese hyperuricemia inoculated with xanthine dehydrogenase- (XOD-) producing bacteria, Streptococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…An analysis of CoTOL targeted bacteria in a mouse model of obesity HUA inoculated with the XDH-producing bacterium Streptococcus faecalis. The results showed that the S. faecalis inoculation resulted in elevated UA and altered the gut microbiota structure, while the CoTOL treatment increased the abundance of Akkermansia and decreased the abundance of Bacteroides and Alloprevotella ( Gao et al., 2020 ). In gouty arthritis model mice, Simiao Decoction can effectively reduce the serum UA levels, reduce myeloperoxidase (MPO), XOD, and adenosine deaminase (ADA) activities, and relieve gout-related symptoms such as foot swelling and pain ( Lin et al., 2020 ).…”
Section: Gut Microbiota As a Potential Therapeutic Target In Hua And ...mentioning
confidence: 99%
“…An analysis of CoTOL targeted bacteria in a mouse model of obesity HUA inoculated with the XDH-producing bacterium Streptococcus faecalis. The results showed that the S. faecalis inoculation resulted in elevated UA and altered the gut microbiota structure, while the CoTOL treatment increased the abundance of Akkermansia and decreased the abundance of Bacteroides and Alloprevotella ( Gao et al., 2020 ). In gouty arthritis model mice, Simiao Decoction can effectively reduce the serum UA levels, reduce myeloperoxidase (MPO), XOD, and adenosine deaminase (ADA) activities, and relieve gout-related symptoms such as foot swelling and pain ( Lin et al., 2020 ).…”
Section: Gut Microbiota As a Potential Therapeutic Target In Hua And ...mentioning
confidence: 99%
“…Of importance, SISH intervention substantially rescued the relative abundance of those intestinal florae in hyperuricemic rats ( Figure 3 f, Supplementary Figure S2 ). Specifically, SISH enhanced the relative abundance of probiotics such as Akkermansia and Alistipes and reduced the Streptococcus (XOD-producing bacteria) population [ 10 ]. Taken together, these results evidenced that SISH could modulate the gut microbial organization and enhance the microbial diversity in hyperuricemic rats.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the hyperuricemic group, the SISH group had a significantly increased abundance of Ruminococcaceae (unidentified_ Ruminococcaceae , Oscillibacter , Ruminiclostridium , Intestinimonas ) which are considered butyrate-producing prebiotics [ 51 ]. In addition, SISH also increased the abundance of probiotics ( Akkermansia , Alistipes ) and reduced the population of the XOD-producing bacteria ( Streptococcus ) [ 10 ]. Lactobacillus is known to sequentially degrade UA to urea by synthesizing uricase, allantoinase, and allantoicase, thereby improving UA excretion [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al found that the traditional Chinese medicine (TCM) formula, Si-miao-tang, could reduce intestinal apoptosis by inhibiting the expression of NLRP3 inflammatory vesicles, regulating the expression of TNF- α , caspase 8, and AIFM1 proteins, and regulating the expression of APOB, LPL, and PPAR α proteins to affect lipid metabolism and restore intestinal flora [ 116 ]. Gao et al found that the TCM formula, CoTOL, could reduce body weight and uric acid in mice with hyperuricemia models by regulating intestinal flora [ 117 ]. The herbal chicory extract can reduce the activity of key enzymes of uric acid metabolism in hyperuricemic quail, which may be related to regulating intestinal flora and intestinal tight junction protein occludin, increasing the number of beneficial intestinal flora and reducing the number of pathogenic bacteria [ 118 ].…”
Section: Research Status Of Anti-ga Mechanisms In Tcmmentioning
confidence: 99%